Social mindfulness predicts concern for nature and immigrants across 36 nations - Kirkland, K.; van Lange, P.A.M.; van Doesum, N.J.; Acevedo-Triana, C.; Amiot, C.E.; Ausmees, L.; Baguma, P.; Barry, O.; Becker, M.; Bilewicz, M.; Boonyasiriwat, W.; Castelain, T.; et al. (Nature Research, 2022)
People cooperate every day in ways that range from largescale contributions that mitigate climate change to simple actions such as leaving another individual with choice – known as social mindfulness. It is not yet clear whether and how these complex and more simple forms of cooperation relate. Prior work has found that countries with individuals who made more socially mindful choices were linked to a higher country environmental performance – a proxy for complex cooperation. Here we replicated this initial finding in 41 samples around the world, demonstrating the robustness of the association between social mindfulness and environmental performance, and substantially built on it to show this relationship extended to a wide range of complex cooperative indices, tied closely to many current societal issues. We found that greater social mindfulness expressed by an individual was related to living in countries with more social capital, more community participation and reduced prejudice towards immigrants. Our findings speak to the symbiotic relationship between simple and more complex forms of cooperation in societies.
Keywords: Immigration; Mindfulness; Psychology; Data science; Political science; Clinical psychology; Computer science; https://purl.org/pe-repo/ocde/ford#5.01.01